MFG-E8 alleviates intervertebral disc degeneration by suppressing pyroptosis and extracellular matrix degradation in nucleus pulposus cells via Nrf2/TXNIP/NLRP3 axis - Haiwei Ma; Chenglong Xie; Zhengtai Chen; Gaolu He; Zihan Dai; Hanchen Cai; Haojie Zhang; Hongwei Lu; Hongqiang Wu; Xinli Hu; Kailiang Zhou; Gang Zheng; et al. (Cell Death Discovery, 2022)
Abstract Intervertebral disc degeneration (IVDD) is a chronic age-related degenerative disease accompanied by complex pathophysiological mechanisms. Increasing evidence indicates that NLRP3 inflammasome mediated pyroptosis of nucleus pulposus (NP) cells displays an important role in the pathological progression of IVDD. Milk fat globule-EGF factor-8 (MFG-E8) is an endogenously secreted glycoprotein with beneficial effects of anti-inflammatory, antioxidant, and modulation of NLRP3 inflammasome. However, the effect of MFG-E8 on IVDD remains unclear. In this study, our purpose is to clarify the expression changes of MFG-E8 in the IVDD process and explore the role and mechanism of MFG-E8. We found that MFG-E8’s expression was reduced in degraded nucleus pulposus tissues of humans and rats as well as hydrogen peroxide (H2O2)-treated NP cells. Exogenous supplementation of MFG-E8 could rescue H2O2-induced oxidative stress, mitochondrial dysfunction, and NLRP3 inflammasome activation and protect NP cells from pyroptosis and extracellular matrix (ECM) degradation. Mechanistically, Nrf2/TXNIP/NLRP3 axis plays a crucial role in MFG-E8-mediated suppression of the above-pathological events. In vivo, we established a rat intervertebral disc acupuncture model and found that MFG-E8 administration effectively alleviated IVDD development by imageological and histomorphological evaluation. Overall, our findings revealed the internal mechanisms underlying MFG-E8 regulation in NP cells and its intrinsic value for IVDD therapy.